DISCLOSURE OF BANK CUSTOMER DECISIONS USING QRIS AS A MEANS OF ONLINE TRANSACTIONS IN THE DIGITAL ERA - Zulhawati; Meiliyah Ariani; Avinash Pawar (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to find out the factors that affect bank customers' decision to use QRIS as a means of online transactions in the digital era for BCA bank customers in Central Jakarta. The type of research used in this research is quantitative research.  Meanwhile, the data used in the study is primary data. The data collection technique in this study is by means of interviews and questionnaire distribution. The sample in this study uses an accidental sampling technique of 105 people who are customers of Bank BCA in Central Jakarta. The data analysis in this study used multiple linear regression with the SPSS 26 For Windows statistical application program. The results of this study show that social strata have a positive effect on customers' decisions to transact using QRIS, this proves that the higher a person's social strata, the more likely they are to choose to use QRIS in making transactions. Higher social strata tend to be more open to the use of new technologies compared to customers from lower social strata.  Lifestyle has a positive effect on customers' decisions to transact using QRIS, this proves that the more modern, dynamic, and consumptive a person's lifestyle, the greater their tendency to choose QRIS as a transaction method. Trust has a positive effect on customers' decisions to transact using internet banking, proving that the higher the level of customer trust in QRIS, the more likely they are to use this transaction method.